Multi-sensory interactive interior design for enhancing skills in children with autism - Aya Lotfy Zakarya Habbak; Laila Khodeir (Ain Shams Engineering Journal, 2023)
The sensitivity of children with autism to interior space elements differs from their healthy peers. Accordingly, there was a need to make a study on their sensitivity to internal elements, then study how to use that to enhance their skills. This paper aims to introduce different types of spatial design for children with autism and their sensitivity to interior elements and then use that to enhance their abilities through multi-sensory rooms. To achieve that aim several research methodologies were implemented starting with a literature review, and site visits to the rehabilitation centers, then a survey was conducted to measure the sensitivity of children with autism to interior space elements and how the elements of multi-sensory rooms enhance their abilities. The findings of this paper have enclosed that children with autism are more sensitive to light than any other element in the interior space, therefore, light is used to develop their skills in the multisensory room.